Regulating Innovative Activity: the Role of a Public Firm - Flavio Delbono; Vincenzo Denicolò (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1991)
Without spillovers and under the "winner-take-all" hypothesis, there is overinvestment in R&D in a non cooperative equilibrium. This is due to the so-called "common pool problem", i.e., duplication of efforts. We show that a public firm can represent a useful instrument in the hands of a policymaker to mitigate such a problem. More precisely, it is provided that, in a mixed duopoly: (i) each firm invest less than in a private duopoly, (ii) although the expected time of innovation is postponed, social welfare is higher than in a private duopoly.
Keywords: 330